2015
DOI: 10.1007/s12035-015-9101-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypothyroxinemia-Induced Neurodevelopmental Impairments in the Progeny

Abstract: Maternal hypothyroxinemia can induce neurodevelopmental impairments in the developing fetus. We here review recent studies on the epidemiology and molecular mechanisms associated with this important public health issue. In 2011, the American Thyroid Association defined maternal hypothyroxinemia as low serum free thyroxine (FT4) levels (<5th or <10th percentile) existing in conjunction with normal serum free triiodothyronine (FT3) or thyroid stimulating hormone (TSH) levels during pregnancy. Compared to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 117 publications
1
41
0
2
Order By: Relevance
“…The importance of thyroid hormone to fetal brain development has been less characterized, but it is well established that maternal thyroid status is also intricately involved in the developing fetal brain (Eayrs, ; Lavado‐Autric et al., ; Patel, Landers, Li, Mortimer, & Richard, ; Stenzel & Huttner, ). Maternal thyroid dysfunction generally ensues in response to several factors such as iodine deficiency, environmental endocrine disrupters, or intrinsic thyroid diseases (Min et al., ). World Health Organization (WHO) has declared that iodine deficiency is, after starvation, the single most important cause of preventable brain damage, by affecting thyroid function (Morreale de Escobar et al., ; WHO, ).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of thyroid hormone to fetal brain development has been less characterized, but it is well established that maternal thyroid status is also intricately involved in the developing fetal brain (Eayrs, ; Lavado‐Autric et al., ; Patel, Landers, Li, Mortimer, & Richard, ; Stenzel & Huttner, ). Maternal thyroid dysfunction generally ensues in response to several factors such as iodine deficiency, environmental endocrine disrupters, or intrinsic thyroid diseases (Min et al., ). World Health Organization (WHO) has declared that iodine deficiency is, after starvation, the single most important cause of preventable brain damage, by affecting thyroid function (Morreale de Escobar et al., ; WHO, ).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…The importance of thyroid hormone to fetal brain development has been less characterized, but it is well established that maternal thyroid status is also intricately involved in the developing fetal brain (Eayrs, 1953;Lavado-Autric et al, 2003;Patel, Landers, Li, Mortimer, & Richard, 2011;Stenzel & Huttner, 2013). Maternal thyroid dysfunction generally ensues in response to several factors such as iodine deficiency, environmental endocrine disrupters, or intrinsic thyroid diseases (Min et al, 2015).…”
Section: Maternal Thyroid Dysfunction and Fetal And Postnatal Neuromentioning
confidence: 99%
“…However, data on the later phases of pregnancy are less concordant [54]. A recent metanalysis concluded that there is a 3-fold increased risk of child cognitive impairment when hypothyroxinemia is detected in mothers during gestation, although the big heterogeneity among the definitions of cognitive delay, the tests performed, and the assessment periods limits these findings [59]. In terms of iodine supplementation, another metanalysis concluded that, at present, the literature data are undermined by low evidence and several limitations, and no clear benefits or risks of iodine supplementation on children’s outcomes can be summarized [60].…”
Section: Maternal Hypothyroidismmentioning
confidence: 99%
“…Our previous research findings suggested that hypothyroxinaemia caused by mild ID affected dendritic development of cerebellar purkinje cells (PCs), the proliferation of cerebellar granule neuron precursors (CGNPs), and differentiation of cerebellar granular cells (Wang et al, 2014a,b; Dong et al, 2016; Min et al, 2016a). As the most important neuron in the cerebellum, PCs summate all of stimulations to the cerebellum and are the only efferent nerves of the cerebellum (Palay and Chan-Palay, 1974).…”
Section: Introductionmentioning
confidence: 99%